Blutung als Leitsymptom in der Notaufnahme - Schmid, Bonaventura; Hodel, Karin; Busch, Hans-Jörg (DMW - Deutsche Medizinische Wochenschrift, 2019)
Acute bleeding is a common and challenging condition in the emergency room. The need for staff and medical resources in these patients depends on the clinical status and extent of the bleeding. The causes of acute bleeding are heterogeneous. Patients may appear in an emergency department with gastrointestinal, traumatic, intracerebral, gynecological or urological bleeding. Bleeding may be triggered or aggravated by underlying diseases or the use of anticoagulants or antiplatelet therapy. The treatment can range from general measures to complex intensive care with antidotes, blood coagulation and transfusion management. Nevertheless, the initial management in such cases is often the same.The purpose of this article is to give an overview of the different types of acute bleeding in an emergency room and how to overcome these specific challenges. Important is the initial management with appropriate general measures to stabilize the patient to avoid serious complications. It is helpful to set up structured processes for these cases.
Keywords: Notfallmedizin; akute Blutung; Antikoagulation; Transfusion